Electronic Structural Origin of the Catalytic Activity Trend of Transition Metals for Electrochemical Nitrogen Reduction - Yeo, Byung Chul; Kong, Jimin; Kim, Donghun; Goddard, William A., III; Park, Hyun S.; Han, Sang Soo (American Chemical Society, 2019)
As an alternative to the conventional Haber-Bosch process for NH3 synthesis that operates under harsh conditions, an electrochemical process has recently been pursued. Here, using a joint experiment-density functional calculation approach, we determine the activity trend of four transition metals (TMs) (Fe, Ru, Rh, and Pd) for N-2 reduction to NH3: Fe > Ru > Pd > Rh, where the protonation step of *N-2 to form *N2H (* indicates surface sites) is a potential determining step (PDS). The activity trend of the electrocatalysts is determined by the ability of the adsorbate (*N-2 ) over the catalyst surfaces to easily obtain electrons at the PDS with an assumption of a scaling relationship between the activation energy barrier and the free energy difference. In electronic structures, the ability can be estimated by the energy difference between the lowest unoccupied molecular orbital (LUMO) of the adsorbed N-2 on the TM surfaces and the fermi energy (E-F). For early TMs (e.g., Sc and Ti) where the PDS is *NH protonation reaction to form *NH2, the activity of the TMs can be similarly explained with an electronic structural feature that is the energy difference between the LUMO of the *NH and the E-F. Based on the origin, we additionally consider 10 TMs (Ni, Cr, Mn, Co, Cu, Mo, Ag, W, Pt, and Au) and then determine the activity trend of the total 16 diverse TMs for NH3 synthesis. We expect that this work could pave the way to novel alloy catalysts with a high activity for electrochemical NH3 synthesis.
Keywords: AMMONIA-SYNTHESIS; LOW-TEMPERATURE; N-2; PRESSURE; NH3